THE RELATIONSHIP AMONG LEARNING MOTIVATION AND LEARNING ENVIRONMENT AT HOME WITH MATHEMATICS LEARNING OUTCOMES - Ilma Surya Fadhilah; Uswatun Khasanah (Universitas Ahmad Dahlan, 2019)
Many factors influence learning outcomes in students. Motivation to learn and learn about the environment at home was expected to impact students' learning outcomes. The research intends to know whether there are any positive correlation and significance between Motivation to Learn and Learning Environment at Home with Mathematics Learning Outcomes in Students Class VIII of SMP Muhammadiyah 2 Kalasan Sleman in Even Semester in Academic Year of 2018/2019. The population in this research was the students of VIII grade in Junior High School (SMP) Muhammadiyah 2 Kalasan Sleman in Even Semester in Academic Year of 2018/2019, consisted of class VIII A, VIII B, VIII C, VIII D, and VIII E totaling 160 students. Samples were taken by the random sampling technique so that class VIII A was obtained as the research sample class. The writer uses the questionnaire method to collect the data of motivation to learn and the learning environment at home and the documentation technique to get the resulting learning of math. The research instrument: validity test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed no positive and significant relationship between Motivation to Learn and Learning Environment at Home with Mathematics Learning Outcomes in Students Class VIII of SMP Muhammadiyah 2 Kalasan Sleman in Even Semester in Academic Year 2018/2019. It is showed by Fcount Ftable is 1,784207393 < 3.3048172522 with R = 0,3260410241 and R2 = 0,106302749 with , with RC = and RC = , EC = and EC = .